Dampak E-commerce terhadap perilaku konsumen dan pembelanjaan di era digital - Ainurrohmah, Cindy (Maliki Interdisciplinary Journal, 2024)
Currently, buying and selling activities have changed due to technological developments that act as a supporting medium in the business sector. The impact of this technological development is the emergence of online trading or e-commerce. This paper discusses the impact of e-commerce on consumer behavior and spending in the digital era. The object of writing on online libraries, Google Scholar, and other online academic media. The research method is through library research sourced from open access e-journals and e-books. The results of writing this article are the role of technology and innovation in influencing consumer behavior, increasing accessibility and ease of shopping, the impact of e-commerce on spending, and the benefits of e-commerce in the digital era. E-commerce in the digital era provides convenience for consumers in shopping, such as ease of transactions, but also the ability to save energy and time in buying and selling. E-commerce has positive and negative impacts depending on how it is used.